Histomorphological effects of ß,Ɛ-Carotene-3,3’-diol on the liver following indomethacin-induced hepatotoxicity in adult male Wistar rats - Ofusori, Adebimpe Esther; Raharjo, Yanuardi; Ofusori, David Adesanya; Adekunle, Victory Opeyemi (Journal of Medicinal Herbs and Ethnomedicine, 2024)
Medicinal plants are globally used as food and in the management of different ailments based on their peculiar phytochemical contents. This study aimed to evaluate the histomorphological effects of ß,Ɛ-Carotene-3,3’-diol on the liver following indomethacin-induced hepatotoxicity in adult male Wistar rats. This is to determine the ameliorative effect of graded doses of ß,Ɛ-Carotene-3,3’-diol. A total of twenty-five adult Wistar rats were randomly divided into five groups (n=5). Liver injury was induced by oral administration of 20 mg/kg b.w of indomethacin after 24 hours fast to animals in groups B-E. Twenty four hours after the induction, animals in groups C-E were given different doses of ß,Ɛ-Carotene-3,3’-diol. At the end of the experimentation, the animals were sacrificed and the livers were collected and fixed for histopathological and histomorphological analyses. The results showed that indomethacin increased the activities of AST, ALT and ALP and also induced histopathological changes. Treatment with ß,Ɛ-Carotene-3,3’-diol was able to attenuate liver injury caused by indomethacin in a dose dependent manner as evidenced in the histoarchitectural changes. This was also corroborated by the histomorphometric analyses. In conclusion, the results suggested the positive influence of ß,Ɛ-Carotene-3,3’-diol in ameliorating liver injury caused by indomethacin and by extension, may be adopted in the management of liver related injury.